The Effect of Alternative Fuel on the On-Board Diagnostics System at Compression-Ignition (Diesel) Combustion Engines - Michal Angelovič; Juraj Jablonický (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of our study was to monitor the alterations of the on-board diagnostics (OBD) system of compression-ignition combustion engines, when alternative fuels were used as a source of energy. We described a theory of emissions formation, diagnostics of standards defects of diesel engines and the formation of opacity. We also focused on processing and evaluation of readiness code, which is used to control various functions of the engine. Diesel fuel and alternative fuel were used for realized measurements in accordance with selected methodology. By means of measurements, we detected conditions of readinesscode and the coefficient values of light absorption factors of exhaust gases. Compared to the reference fuel, we detected no alterations in readinesscode, when we monitored the impact of fuel on the on-board diagnostics system. The components controlled by on-board diagnostics system (complex components, fuel system, exhaust gas recirculation) operate with the alternative fuel without detected defects of conditions.